2017
DOI: 10.4330/wjc.v9.i9.723
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo cardiomyopathy: Pathophysiology and role of cardiac biomarkers in differential diagnosis

Abstract: Takotsubo cardiomyopathy (TC) is characterized by reversible ventricular dysfunction, not limited to the distribution of an epicardial coronary artery. A disease primarily afflicting post-menopausal women, it is frequently mistaken for acute anterior wall myocardial infarction. Alternatively called Stress Cardiomyopathy, physical or emotional triggers are identified in only three fourths of TC patients. Long considered a benign condition, recent findings suggest poor short term prognosis similar to acute coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 50 publications
1
22
1
5
Order By: Relevance
“…The criteria used to diagnose Takotsubo cardiomyopathy have been described in detail by the Mayo Clinic [5], and it is essential to exclude significant organic stenosis or coronary artery spasm. Although women have a 9-fold higher risk of developing this cardiomyopathy when compared to men, women who are less than 55 years of age have a 5-fold risk reduction of developing the cardiomyopathy when compared to women who are older than 55 years of age [6]. Therefore, the case reported here was not at a common age for development of Takotsubo cardiomyopathy.…”
Section: Discussionmentioning
confidence: 76%
“…The criteria used to diagnose Takotsubo cardiomyopathy have been described in detail by the Mayo Clinic [5], and it is essential to exclude significant organic stenosis or coronary artery spasm. Although women have a 9-fold higher risk of developing this cardiomyopathy when compared to men, women who are less than 55 years of age have a 5-fold risk reduction of developing the cardiomyopathy when compared to women who are older than 55 years of age [6]. Therefore, the case reported here was not at a common age for development of Takotsubo cardiomyopathy.…”
Section: Discussionmentioning
confidence: 76%
“…The gold standard for diagnosis of TC is to use radio-contrast dye with a ventricular flow study to assess contraction of the ventricle [8]. In TC, the left ventricle fails to contract at the bottom (akinesia), with normal contraction towards the atrial end of the ventricle.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies observed that cardiac biomarkers such as cardiac troponin I (cTnI) and B-type natriuretic peptide (BNP) may play a role in the early clinical recognition of SCM. However, to the best of our knowledge, data is limited regarding the pattern in which cardiac biomarkers are released in patients with SCM [6,7]. In addition, the changes in myocardial function during IMO stress and the optimal measurement time point are still unknown, even though this is of clinical importance [3].…”
Section: Introductionmentioning
confidence: 99%